Infestasi Lalat Buah (Bactrocera spp.) Pada Buah Jambu Air Madu (Syzygium samarangense) di Sumatera Utara - Putri, Kartika Aprilia (Department of Biology Education, Faculty of Teacher Training and Education, Samudra University, 2019)
Cultivation of wax apple (Syzygium samarangense) is one source of livelihoods in North Sumatra, Indonesia. However, the obstacles encountered in harvesting period are fruit fly infestation which decreases the economic value. The purpose of this study was to identify the species of fruit fly infested on wax apple S. samarangense and its parasitoid . Thirty kilos of infested wax apple was collected from the field (at Stabat regency : North Sumatera) by purposive sampling and bring to the laboratory, stored in a bucket for the periods of 7 to 10days. All the pupae place individually in plastic tube until emergence. Adult flies and its parasitoid were collected for further identification in separate cages. Identification was done using morphological characters such as the T shape of the abdomen, the wings, the shape of the thorax, the length of cell dm and aedeagus length. From 30 kilos of wax apple found 427 pupae which consist of 250 pupae emerge as fruit flies and 20 pupae emerge as parasitoid. Based on morphological character of fruit flies there were 4 species of Bactrocera spp (B.albistrigata, B.dorsalis, B.papayae and B.carambolae). The number of individuals for B.albistrigata was 50, B. dorsalis was 56, B. papaya was 73 and B. carambolae was 71. Measurement of aedeagus and cell dm length was varied between species. Aedeagus and cell dm length of B.dorsalis were 2.69 ± 0.5 mm and 2.28 ± 0.35 mm, B. papayae were 2.64 ± 0.49 mm and 2.23 ± 2.23 mm, and B. carambolae were 2.43 ± 0.28 and 1.9 ± 0.26 mm. The parasitoids found from infested fruit were Fopius vandenboschi, Psyttalia sp. and Diachasmimorpha longicaudata.